Management of phytopathogens by application of green nanobiotechnology: Emerging trends and challenges - Rai, Mahendra; Kratosova, Gabriela (Acta Agraria Debreceniensis, 2015)
Nanotechnology is highly interdisciplinary and important research area in modern science. The use of nanomaterials offer major advantages due to their unique size, shape and significantly improved physical, chemical, biological and antimicrobial properties. Physicochemical and antimicrobial properties of metal nanoparticles have received much attention of researchers. There are different methods i.e. chemical, physical and biological for synthesis of nanoparticles. Chemical and physical methods have some limitations, and therefore, biological methods are needed to develop environment-friendly synthesis of nanoparticles. Moreover, biological method for the production of nanoparticles is simpler than chemical method as biological agents secrete large amount of enzymes, which reduce metals and can be responsible for the synthesis and capping on nanoparticles.Biological systems for nanoparticle synthesis include plants, fungi, bacteria, yeasts, and actinomycetes. Many plant species including Opuntia ficus-indica, Azardirachta indica, Lawsonia inermis, Triticum aestivum, Hydrilla verticillata, Citrus medica, Catharanthus roseus, Avena sativa, etc., bacteria, such as Bacillus subtilis, Sulfate-Reducing Bacteria, Pseudomonas stutzeri, Lactobacillus sp., Klebsiella aerogenes, Torulopsis sp., and fungi, like Fusarium spp. Aspergillus spp., Verticillium spp., Saccharomyces cerevisae MKY3, Phoma spp. etc. have been exploited for the synthesis of different nanoparticles. Among all biological systems, fungi have been found to be more efficient system for synthesis of metal nanoparticles as they are easy to grow, produce more biomass and secret many enzymes. We proposed the term myconanotechnology (myco = fungi, nanotechnology = the creation and exploitation of materials in the size range of 1–100 nm). Myconanotechnology is the interface between mycology and nanotechnology, and is an exciting new applied interdisciplinary science that may have considerable potential, partly due to the wide range and diversity of fungi.Nanotechnology is the promising tool to improve agricultural productivity though delivery of genes and drug molecules to target sites at cellular levels, genetic improvement, and nano-array based gene-technologies for gene expressions in plants and also use of nanoparticles-based gene transfer for breeding of varieties resistant to different pathogens and pests. The nanoparticles like copper (Cu), silver (Ag), titanium (Ti) and chitosan have shown their potential as novel antimicrobials for the management of pathogenic microorganisms affecting agricultural crops. Different experiments confirmed that fungal hyphae and conidial germination of pathogenic fungi are significantly inhibited by copper nanoparticles. The nanotechnologies can be used for the disease detection and also for its management. The progress in development of nano-herbicides, nano-fungicides and nano-pesticides will open up new avenues in the field of management of plant pathogens. The use of different nanoparticles in agriculture will increase productivity of crop. It is the necessity of time to use nanotechnology in agriculture with extensive experimental trials. However, there are challenges particularly the toxicity, which is not a big issue as compared to fungicides and pesticides.